Prevalence of Common Methods of Suicide among Iranian Men; a Systematic Review - Moamer, Soraya; Hajinasrollah, Ghazal; Aliakbari , Freshet; Nasehi, Abbas Ali; Samadaee Gelehkolaee, Keshvar; Hosseini, Jalil (Archives of Men’s Health, 2023)
Background: Suicide is one of the public health problems with a high rate worldwide. Sex is a risk factor for successful suicide, making it the seventh leading cause of death in men in the United States. Based on the increasing suicide rate in Iran, we aimed to investigate the common methods of suicide in Iranian men. Methods: This study is a systematic review with subgroup analysis based on the prevalence of methods of suicide in Iranian men during 2009-2019. Specific keywords based on medical subject headings (MeSH) were searched in Iranian and international databases including PubMed, Scopus, Google Scholar, SID, and MagIran by designing a search strategy. Selected studies were reviewed using the study evaluation tool. For data analysis, STATA software version 14 was used. Also, heterogeneity studies by Q and I2 statics were assessed. Results: In the first phase, 529 studies were extracted, and finally, data were extracted from 19 studies. Because of the heterogeneity of the studies, meta-analysis was not possible and the final results were extracted based on subgroup analysis. Drug abuse was the most common method of suicide and the use of firearms was the least prevalent among Iranian men. Conclusion: Currently, the most common method of suicide in Iranian men is drug abuse. Therefore, it is recommended to design preventive interventions based on gender and take into account commonly available methods.